Predicting extinction risk in declining species. - Purvis, A (2000)
What biological attributes predispose species to the risk of extinction? There are many hypotheses but so far there has been no systematic analysis for discriminating between them. Using complete phylogenies of contemporary carnivores and primates, we present, to our knowledge, the first comparative test showing that high trophic level, low population density slow life history and, in particular, small geographical range size are all significantly and independently associated with a high extinction risk in declining species. These traits together explain nearly 50% of the total between-species variation in extinction risk. Much of the remaining variation can be accounted for by external anthropogenic factors that affect species irrespective of their biology.